Al Khusr in the Qur'an - Fadhliah Mubakkirah; Rahmi D; Ahmad Mujahid (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2026)
This article examines the moral crisis and dehumanization of modern society through the Qur'anic concept of al-khusr. The imbalance between technological advancement and the cultivation of character has triggered moral, social, and spiritual degradation. Drawing on verses such as QS al-'Aṣr, al-A'rāf 179, and al-Kahf 103–104, this condition is interpreted as a multidimensional loss caused by the erosion of faith, righteous deeds, commitment to truth, and patience. Employing a qualitative method through library research and thematic exegesis, the study identifies Qur'anic verses related to al-khusr and evaluates their relevance to the contemporary moral crisis. The findings show that al-khusr is not limited to eschatological loss in the hereafter, but also encompasses the collapse of human existence, the disappearance of moral orientation, the weakening of spiritual awareness, and the deterioration of social order. A contextual interpretation indicates that the concept of al-khusr serves as a normative framework for diagnosing the roots of the moral crisis while offering a Qur'an-based direction for restoring human dignity. Abstrak Artikel ini membahas krisis moral dan dehumanisasi masyarakat modernmelalui perspektif al-khusr dalam Al-Qur’an. Ketimpangan antara kemajuan teknologi dan penguatan karakter menyebabkan degradasi moral, sosial, danspiritual. Berdasarkan ayat-ayat seperti QS. al-‘Aṣr, al-A‘rāf 179, dan al-Kahf 103–104, kondisi tersebut dipahami sebagai kerugian multidimensi akibat hilangnya iman, amal saleh, komitmen pada kebenaran, dan kesabaran. Penelitian menggunakan metode kualitatif dengan studi kepustakaan dananalisis tafsir tematik untuk mengidentifikasi ayat-ayat terkait al-khusr dan menilai relevansinya terhadap kerusakan moral kontemporer. Hasilnya menunjukkan bahwa al-khusr bukan hanya kerugian akhirat, tetapi juga mencakup keruntuhan eksistensi manusia, hilangnya orientasi moral, melemahnya kesadaran spiritual, dan terganggunya tatanan sosial. Penafsiran kontekstual menegaskan bahwa konsep al- khusr dapat dijadikan kerangka normatif untuk mendiagnosis akar krisis moral dan menawarkan arah pemulihan martabat kemanusiaan berbasis nilai Qur’ani.